PERAN PERUSAHAAN TERHADAP KESEHATAN DAN KESELAMATAN KERJA PADA PT. CIPTA PRIMA - Kristoper Hansen; Carla Olyvia Doaly (PROSIDING SERINA, 2021)
Occupational Health and Safety is one of the things that companies must pay attention to for their workers, so that workers will feel comfortable and safe when they will work for a company. PT. Cipta Prima itself has several standards for occupational health and safety that are applied to its company. The standards applied to its workers are the use of Personal Protective Equipment or PPE (Gloves, Shoes and Masks), handling of emergencies, handling of work accidents, inspection and maintenance of machines as well as prohibition of smoking and carrying dangerous equipment in the factory area. The method used to assess the severity of work accidents that occurred at PT. Cipta Prima is the HIRADC method using likelihood and severity indicators and then calculated with a risk matrix. The results obtained from the analysis tend to be mild to moderate types of accidents caused by careless workers and the lack of signs listed in the factory so that workers often forget to wear personal protective equipment that has been set according to factory standards. Several solutions to reduce work accidents at PT. Cipta Prima includes rearranging goods and production equipment, supervising workers, adding K3 signs in the factory area, and routinely conducting briefings on K3 and periodic maintenance on machines.